Specific Features of Development of the Russian Modern Art Market: Analysis of Krasnoyarsk Krai - Anastasia M. Obmorokova; Natalia O. Nemaeva; Gennady E. Karepov (International Review of Management and Marketing, 2016)
This paper analyzes the modern art market of Russia. It gives special importance to the regional art market's specific features and "new media" as one of its elements. The purpose of this paper is to study market processes in the modern art sphere of Central Siberia (Krasnoyarsk Krai). The main methods used to study are analytical reviews of foreign and domestic sources with regard to the given subject, studies of digital-marketing strategies, surveys and in-depth interviews. It is established that the dynamics of the regional art market in Krasnoyarsk directly depend upon such factors as communication and information digital technologies that are actively used by modern artists in order to create and maintain their prestige, as well as to increase their competitiveness. The paper establishes forecasts for the future of the Krasnoyarsk modern art market, including its general place in the structure of the art market of Russia, and the prospects of development of the regional fine art market.